Strategi Pemasaran Asuransi Syariah di Indonesia - Muhammad Al Fazri; Nuri Aslami (VISA: Journal of Vision and Ideas, 2021)
Sharia insurance, also known as takaful, at-ta'min, or tadhamun, is an effort to help and protect each other between participants whose operational and legal principles are based on Islamic law. Without intending to precede destiny, insurance can be intended as a preparation effort to deal with possible risks. Sharia insurance itself has the potential to grow along with the increase in the Islamic financial market in Indonesia. The purpose of this paper is to find out how sharia insurance marketing strategies and tactics are to be easily accepted by the community. This study uses a literature review or library research with a descriptive approach which is part of the qualitative. Keywords: Sharia Insurance, Marketing strategy, Marketing tactics.